The Effect of Company Size, Profitability, and Liquidity on Capital Structure of Manufacturing Companies in Indonesia's Food and Beverage Sector - Syaimila, Iski Mila; Mursidi, Mursidi; Rahadjeng, Erna Retna (Universitas Muhammadiyah Malang, 2023)
This study aims to examine the effect of company size, profitability, and liquidity on the capital structure of manufacturing companies in the food and beverage sector in Indonesia. The population in this study were all real estate companies listed on the IDX in 2020-2022. Using a purposive sampling technique, a sample of 16 companies was obtained. This method uses multiple linear regression with SPSS Version 27. The results of this study concluded that company size and profitability partially have no significant effect on capital structure, while liquidity has a significant effect on capital structure. In addition, it can be found that firm size, profitability, and liquidity simultaneously have a significant influence on the capital structure of manufacturing companies.